The Pre-History of the Commentary Tradition : Aristotelianism in the First Century bce: (Prolegomena to a Study of Xenarchus of Seleucia) - Falcon, Andrea (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2008)
AbstractIn the first century bce Aristotle was subject to an intense textual study. This study eventually led to the appropriation of the conceptual apparatus developed in his writings. In the case of Xenarchus, the relevant apparatus was Aristotle’s theory of motion, with an emphasis on the concepts of natural place and natural motion. Xenarchus reworked Aristotle’s theory of motion so as to make the celestial simple body expendable. While I do not deny that some of his views are best understood in light of the debates of late Hellenestic philosophy, I contend that his textual engagement presupposes the distance from Aristotle that is characteristic of Post-Hellenistic philosophy.